PEMBERDAYAAN PELAKU USAHA IKAN PATIN MELALUI IMPLEMENTASI DIGITAL SUPPLY CHAIN MANAGEMENT DI KECAMATAN 13 KOTO KAMPAR [EMPOWERING PATIN FISH BUSINESS ACTORS THROUGH THE IMPLEMENTATION OF DIGITAL SUPPLY CHAIN MANAGEMENT IN DISTRICT 13 KOTO KAMPAR] - Nasari, Fina; Veronika, Nina; Deli, Nur Asma; Akbar, Rahmad; Habibie, Indra; Nurkholifah, Mahdiawan; Amelia, Suci Fitri (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This Community Service Program aims to enhance the capacity of patin fish business actors in District 13 Koto Kampar through the adoption of digital technology in production recording, supply chain management, and market information utilization. The main problems faced by the partners include inaccurate manual recording, inefficiencies in distribution, and limited access to data and market opportunities. To address these challenges, the program was carried out through a series of training sessions, technical assistance, demonstrations of digital application usage, and evaluations conducted before and after the activities. The implementation methods focused on improving participants’ skills in adopting digital recording systems, understanding modern supply chain–based distribution flows, and utilizing market information to increase competitiveness. The evaluation results indicate a significant increase in competencies across all measured aspects. The average pre-test and post-test scores improved in Digital Production Recording (from 58 to 84), Supply Chain Management (from 55 to 82), and Market Information Utilization (from 52 to 80). This improvement reflects the success of the program in strengthening the participants’ digital capacities and enhancing the operational efficiency of their businesses. Overall, the program provides positive impacts on the digitalization of local fisheries enterprises while building a stronger foundation for the development of sustainable marketing and distribution strategies.